The process of building a mobile application for the protection of women and the prevention of domestic violence: an experience report (Research, Society and Development, 2023)
Introduction: Violence against women is an active and persistent problem in the history of society. Technology has become a great ally in the development of applications aimed at health care. Goal: In this perspective, the objective of this article is the academic production of a written report of an experience through the idealization and elaboration of a software technology with the purpose of combating and quickly attending events involving domestic violence against women. Methodolody: This article is a descriptive and qualitative study, using Maguerez's problematization arc to structure the research. Results na Discussion: The angel application has a simple and discreet interface, with a button to activate it in case of emergencies. When the victim activates the system, the mobile app will forward her location to the nearest police vehicle, thus enabling an efficient and fast rescue, interfering with the progression of the violent act. Furthermore, the mobile app will produce and store evidence, strengthening the evidence of culpability of the violator of rights and the most consistent and irrefutable defense of the victim. Conclusion: The technological tool has the potential to become a means of control and prevention of cases of domestic violence against women, so it is up to the public agencies to legitimize and appropriate such an instrument to combat domestic violence.